Interaction between perfluorooctanoic acid and aerobic granular sludge. (1st February 2020) - Yang, Guojing; Zhang, Ni; Yang, Jingnan; Fu, Qizi; Wang, Yu; Wang, Dongbo; Tang, Li; Xia, Jingfen; Liu, Xuran; Li, Xiaoming; Yang, Qi; Liu, Yiwen; et al.
Abstract: The increasing use of perfluorooctanoic acid (PFOA) raises concerns about its potential toxicity to the environment. However, the interaction between PFOA and aerobic granular sludge has never been documented. This work therefore aims to provide such support through investigating the fate of PFOA at environmentally relevant levels in aerobic granular sludge systems and its impact on aerobic granular sludge. Experimental results showed that 32.0%∼36.4% of wastewater PFOA was removed by aerobic granular sludge in stable operation when PFOA concentration was ranged from 0.1 to 1.0 mg/L. Mass balance analyses and X-ray photoelectron spectroscopy survey scan revealed that the removal of PFOA was dominated by adsorption rather than biodegradation, and sorption kinetic analysis indicated that inhomogeneous multilayer adsorption was responsible for this removal. The adsorbed PFOA deteriorated the settleability of granular sludge and biological nitrogen and phosphorus removal significantly. Experimental results showed that 1.0 mg/L PFOA inhibited anaerobic phosphate release, aerobic phosphate uptake, nitrate reduction, and nitrite reduction processes by 60%, 50%, 13.1%, and 5.8%, respectively. It was observed that PFOA induced large amounts of filamentous villus growing on the surface and increased the extracellular polymeric substances of granular sludge. Fourier-transform infrared spectra and X-ray photoelectron spectroscopy spectrum showed that several function groups in extracellular polymeric substances such as hydroxyl groups, amides and polysaccharides were affected by PFOA. It was also found that PFOA inhibited the cyclic transformations of polyhydroxyalkanoates and glycogen. Microbial community analyses showed that PFOA decreased the abundances of Nitrosomonas, Nitrospira, Accumulibacter, and other function microbes such as Rhodospirillaceae, Thauera, and Azoarcus . Graphical abstract: Image 1 Highlights: PFOA was removed by aerobic granular sludge mainly through adsorption rather than biodegradation. PFOA deteriorated the settleability and biological nitrogen and phosphorus removal of aerobic granular sludge. Several function groups such as hydroxyl groups, amides and polysaccharides were affected by PFOA. PFOA inhibited the transformations of polyhydroxyalkanoates and glycogen .